Non-aqueous electrolyte secondary battery

By controlling the internal porosity of silicon-containing materials and adding cyclic compound components in non-aqueous electrolyte secondary batteries, the problem of active material breakage caused by volume changes in silicon-containing materials has been solved, resulting in lithium-ion secondary batteries with high capacity retention and long lifespan.

CN123036697APending Publication Date: 2026-11-03PANASONIC ENERGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580025398.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-14
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Silicon-containing materials in lithium-ion secondary batteries experience large volume changes due to the absorption and release of lithium ions, which makes the active material particles prone to breakage, the formation of new surfaces, and the initiation of side reactions, resulting in reduced capacity retention and decreased cycle performance.

Method used

In non-aqueous electrolyte secondary batteries, a negative electrode mixture containing a negative electrode active material is used, wherein the internal porosity of the silicon-containing material particles is more than 6% and less than 20%, and 0.1 to 2% by mass of a cyclic compound containing sulfur, such as 1,3-propenyl sulfonate, is added to form a low-resistivity film and suppress side reactions.

Benefits of technology

It effectively suppressed the decline in cycle characteristics, improved capacity retention and lifetime, and ensured high discharge capacity and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123036697A_ABST
    Figure CN123036697A_ABST
Patent Text Reader

Abstract

A nonaqueous electrolyte secondary battery includes a negative electrode containing a negative electrode mixture, a separator, a positive electrode opposite to the negative electrode with the separator interposed, and a nonaqueous electrolyte. The negative electrode mixture contains a negative electrode active material. The particle internal porosity of the silicon-containing material is 6% or more and 20% or less. The nonaqueous electrolyte contains a 5- or 6-membered cyclic compound component at a concentration of 0.1 to 2% by mass, the 5- or 6-membered cyclic compound component containing sulfur as a ring constituent element.
Need to check novelty before this filing date? Find Prior Art

Description

Cross-references to related applications

[0001] This disclosure claims the benefit of priority to Japanese Patent Application No. 2024-056205, filed on March 29, 2024, with the contents of which are incorporated herein by reference in their entirety. Technical Field

[0002] This disclosure relates to non-aqueous electrolyte secondary batteries. Background Technology

[0003] Non-aqueous electrolyte secondary batteries, such as lithium-ion batteries, consist of a positive electrode, a negative electrode, and a non-aqueous electrolyte. The non-aqueous electrolyte is primarily a non-aqueous liquid. The negative electrode comprises a negative electrode compound containing a negative electrode active material. This active material can be a material capable of electrochemically absorbing and releasing lithium ions. Examples of such materials include carbonaceous materials and silicon-containing materials. Additionally, sometimes carbonaceous materials that do not absorb or release lithium ions, such as carbon fibers and carbon nanotubes, are added to the negative electrode compound as conductive agents.

[0004] Patent document 1 proposes the use of a composite electrode agent in a lithium-ion secondary battery, the composite electrode agent comprising particles containing elements capable of absorbing and releasing lithium ions, carbon particles capable of absorbing and releasing lithium ions, multilayer carbon nanotubes, and carbon nanofibers.

[0005] Patent Document 2 discloses a negative electrode for a non-aqueous electrolyte secondary battery, comprising a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer is supported on the surface of the negative electrode current collector and contains an alloy-based active material for absorbing and releasing lithium ions. A resin layer is also provided on the surface of the negative electrode active material layer, the resin layer containing a resin component with lithium-ion conductivity and an additive for the non-aqueous electrolyte. Examples of non-aqueous electrolyte additives, such as those forming a film on the positive electrode and suppressing gas generation inside the battery at high temperatures, include sulfonyl lactones.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 2014-146519

[0009] Patent Document 2: International Publication No. 2010 / 092815 Summary of the Invention

[0010] The problem that the invention aims to solve

[0011] Silicon-containing materials exhibit significant volume changes during lithium-ion uptake and release. Carbon composite particles, which contain both a carbon phase and a silicon phase dispersed within it, possess high discharge capacity and high utilization of active materials, resulting in particularly large volume changes. Consequently, during repeated charge-discharge cycles, silicon-containing material particles are prone to breakage, creating new surfaces. These new surfaces are susceptible to side reactions with the electrolyte, leading to capacity reduction with repeated charge-discharge cycles, thus decreasing capacity retention and cycle performance.

[0012] Methods for solving problems

[0013] One aspect of this disclosure relates to a non-aqueous electrolyte secondary battery, comprising: a negative electrode containing a negative electrode compound, a separator, a positive electrode separated from the negative electrode by the separator, and a non-aqueous electrolyte, wherein the negative electrode compound contains a negative electrode active material, the negative electrode active material contains a silicon-containing material, the internal porosity of the silicon-containing material particles is 6% or more and 20% or less, and the non-aqueous electrolyte contains a 5- or 6-membered cyclic compound component at a concentration of 0.1% to 2% by mass, wherein the 5- or 6-membered cyclic compound component contains sulfur as a ring-forming element.

[0014] Invention Effects

[0015] In non-aqueous electrolyte secondary batteries using a negative electrode containing carbon composite particles with a silicon phase, the reduction in cycle characteristics can be suppressed.

[0016] The novel features of the invention are set forth in the appended claims; however, the invention should be more fully understood, in both its structure and content, together with its other objects and features, by referring to the following detailed description of the accompanying drawings. Attached Figure Description

[0017] Figure 1 This is a longitudinal cross-sectional view schematically showing the discharge state of the negative electrode (negative electrode compound layer) used in a non-aqueous electrolyte secondary battery according to an embodiment of the present disclosure.

[0018] Figure 2 This is a perspective view of a portion of a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure. Detailed Implementation

[0019] The following examples illustrate embodiments of this disclosure, but this disclosure is not limited to the examples described below. In the following description, specific values ​​and materials are sometimes shown, but other values ​​and materials can be applied as long as the effects of this disclosure are achieved. In this specification, the phrase "value A to value B" includes both value A and value B, and can be replaced with "value A or higher and value B or lower." In the following description, when lower and upper limits of values ​​related to specific physical properties, conditions, etc., are shown, any of the shown lower limits and any of the shown upper limits can be arbitrarily combined, as long as the lower limit is not higher than the upper limit. When multiple materials are shown, one can be selected and used alone, or two or more can be used in combination.

[0020] This disclosure includes a combination of matters described in any two or more claimed technical solutions selected from the plurality of claimed technical solutions described in the appended scope of protection. That is, as long as no technical contradiction arises, matters described in any two or more claimed technical solutions selected from the plurality of claimed technical solutions described in the appended scope of protection can be combined.

[0021] One embodiment of the non-aqueous electrolyte secondary battery disclosed herein includes a negative electrode containing a negative electrode additive, a separator, a positive electrode separated from the negative electrode by the separator, and a non-aqueous electrolyte. The negative electrode additive includes a negative electrode active material. The negative electrode active material includes a silicon-containing material. The internal porosity of the silicon-containing material particles is 6% or more and 20% or less.

[0022] In non-aqueous electrolyte secondary batteries, carbonaceous materials such as graphite are typically used as the negative electrode active material. Silicon-containing materials theoretically have a larger capacity than carbonaceous materials; therefore, by using silicon-containing materials, a higher capacity can be achieved than with carbonaceous materials.

[0023] On the other hand, silicon-containing materials experience significant volume changes during lithium-ion uptake and release, leading to crack formation in active material particles and the easy formation of new surfaces. These new surfaces are prone to side reactions with non-aqueous electrolytes, resulting in capacity reduction. Therefore, even when using silicon-containing materials, capacity retention can sometimes decrease during repeated charge-discharge cycles, making it difficult to ensure a sufficient lifespan.

[0024] Non-aqueous electrolytes contain 5- or 6-membered cyclic compounds in which sulfur is a ring-forming element. Hereinafter, 5- or 6-membered cyclic compounds in which sulfur is a ring-forming element are sometimes simply referred to as "S-containing cyclic compounds." Additionally, silicon-containing materials are sometimes called "Si-containing materials," and the silicon phase is sometimes referred to as the "Si phase" or "silicon phase."

[0025] According to this disclosure, by using a non-aqueous electrolyte containing an S-cyclic compound, even when the negative electrode contains a silicon-containing material, the decrease in capacity retention and the decrease in cycle characteristics can be suppressed. This is believed to be because, during charging and discharging, even if the silicon-containing material develops cracks and new surfaces are formed, a film is formed on the surface of the negative electrode active material due to the S-cyclic compound, suppressing side reactions. Therefore, it is believed that, through the effect of the S-cyclic compound, the film formed on the surface of the silicon-containing material containing the new surfaces is a low-resistance film that does not easily hinder the charging and discharging reaction.

[0026] In contrast, when using carbonaceous materials without the Si phase as the negative electrode active material, even when using a non-aqueous electrolyte containing S-cyclic compounds, the initial discharge capacity and capacity retention during repeated charge-discharge cycles show almost no change compared to a non-aqueous electrolyte without S-cyclic compounds. In other words, as a negative electrode active material, the impact of S-cyclic compounds on cycle performance is significantly different when using carbonaceous materials without the Si phase versus using Si-containing materials with the Si phase.

[0027] On the other hand, the S-containing cyclic compound component helps improve capacity retention by forming a film on the positive electrode, thereby suppressing side reactions occurring on the positive electrode side. However, when using a negative electrode containing silicon-containing materials, the S-containing cyclic compound component, which should function on the positive electrode side, is consumed on the negative electrode side. Towards the end of cycling, numerous cracks form in the silicon-containing material, leading to its micronization and the generation of numerous new surfaces. As a result, the consumption of the S-containing cyclic compound component increases rapidly. Consequently, it is believed that the S-containing cyclic compound component is completely consumed and can no longer function on the positive electrode, thus reaching the end of its lifespan.

[0028] In contrast, in the non-aqueous electrolyte secondary battery of this embodiment, by maintaining an internal porosity of 6% to 20% within the silicon-containing material particles, the active material particles are less prone to breakage, and the formation of new surfaces is suppressed. Therefore, since the micronization of the silicon-containing material at the end of the cycle is suppressed, the consumption of the S-containing cyclic compound component, which is consumed at the negative electrode to form the coating, is significantly reduced. As a result, the S-containing cyclic compound component can function effectively at the positive electrode, thus maintaining a higher capacity retention rate for a longer period, achieving a long-life non-aqueous electrolyte secondary battery.

[0029] The concentration of the S-cyclic compound component in the non-aqueous electrolyte is in the range of 0.1% to 2% by mass. Under this condition, side reactions between the surface of the active material particles containing the newly formed surface and the non-aqueous electrolyte are suppressed, and the capacity retention rate can be maintained at a high level for a long period of time.

[0030] Examples of compounds containing S-ring compounds include those described below, with 1,3-propenylsulfonyl lactone (1-propen-1,3-sulfonyl lactone) being a preferred example.

[0031] Silicon-containing materials can comprise carbon composite particles containing a carbon phase and a silicon phase dispersed within the carbon phase. Carbon composite particles exhibit particularly high utilization of active materials and can achieve large discharge capacities, making them ideal from a high-capacity perspective. However, during repeated charge-discharge cycles, due to volume changes in the silicon phase, not only is the silicon phase prone to cracking, but the carbon phase constituting the matrix is ​​also susceptible to cracking. Therefore, when using carbon composite particles containing a silicon phase, more new surfaces are formed compared to using carbonaceous materials without a silicon phase. Consequently, capacity retention decreases during repeated charge-discharge cycles, and cycling characteristics tend to deteriorate. However, by using a non-aqueous electrolyte containing an S-cyclic compound and ensuring that the porosity within the silicon-containing material (carbon composite particles) is between 6% and 20%, it is possible to ensure the initial high discharge capacity provided by the carbon composite particles and maintain a high capacity retention rate over a long period.

[0032] From the perspective of more significantly suppressing the isolation of carbon composite particles and maintaining abundant non-aqueous electrolytes in the carbon composite particles, the specific surface area of ​​the carbon composite particles can be 5 m². 2 / g or more and 20m 2 / g or less, or 5m 2 / g or more and 16m 2 Below / g, 8m is preferred. 2 / g or more and 16m 2 / g or less, 8m is more preferable. 2 / g or more and 13m 2 / g or less.

[0033] Similarly, from the viewpoint of more significantly suppressing the isolation of carbon composite particles and maintaining abundant non-aqueous electrolytes in the carbon composite particles, the average pore size of the carbon composite particles can be 1 nm or more and 45 nm or less, or 2 nm or more and 45 nm or less, or 5 nm or more and 45 nm or less. The average pore size of the carbon composite particles can be 10 nm or more and 45 nm or less, preferably 15 nm or more and 45 nm or less, and more preferably 15 nm or more and 40 nm or less.

[0034] Here, the specific surface area and average pore size of the carbon composite particles are, in principle, evaluated using carbon composite particles separated from the negative electrode mixture as samples. However, the carbon composite particles are robust and can largely maintain the properties of the raw materials incorporated into the negative electrode mixture. The specific surface area and average pore size of the carbon composite particles reflect both the internal and external voids within the particles.

[0035] For carbon composite particle powder prepared in the manufacture of non-aqueous electrolyte secondary batteries, the specific surface area and average pore size of the carbon composite particles are determined by the following method.

[0036] In the fine pore size distribution of carbon composite particle powder, there are fine pore size distributions caused by the voids between carbon composite particles and fine pore distributions caused by the voids within the carbon composite particles. However, because the fine pore size ranges are different, they can be easily distinguished. In the fine pore volume distribution, the fine pore size X is calculated when the fine pore volume in the range of fine pore size D from 1 nm to X nm is equal to the fine pore volume in the range of fine pore size D from X nm to 500 nm. This value is taken as the average fine pore size of the carbon composite particles.

[0037] A sample of 0.20 g to 0.25 g of carbon composite particles was placed in a measuring cell made of a glass tube used for specific surface area measurement. The sample was dried and degassed within the measuring cell before measurement. The drying and degasing process was carried out at a pressure of 6.67 Pa and a temperature of 250 °C ± 5 °C for at least 1 hour. The mass of the sample in the measuring cell was then measured to a value of 0.1 mg. The amount of nitrogen adsorbed on the sample at -196 °C was then measured using a specific surface area measuring device. Based on the adsorption measurement results, the specific surface area of ​​the carbon composite particles was determined using the BET multi-point method within a partial pressure (relative pressure) range of 0.03 to 1.0.

[0038] Furthermore, the median particle size, representing 50% of the cumulative volume, was calculated based on the fine pore size distribution of the carbon composite particles obtained using the BET multi-point method, and used as the average fine pore size. The fine pore size distribution ranged from 1 nm to 500 nm.

[0039] The internal porosity of silicon-containing materials or carbon composite particles is 6% or more and 20% or less, preferably 8% or more and 20% or less, and more preferably 8% or more and 12% or less. If the internal porosity is 6% or more, a sufficient amount of non-aqueous electrolyte (i.e., lithium ions) can be maintained in the internal voids, allowing a large number of lithium ions to be supplied to the silicon phase without retention during charging, thus maintaining high cycling characteristics. If the internal porosity is 20% or less, while maintaining high capacity, the junction between the silicon phase and the lithium ion conducting phase can be maintained even when the silicon phase expands and contracts during charging and discharging, improving current collection performance. Furthermore, since the strength of the silicon-containing material itself is increased, as mentioned above, the silicon-containing material is less prone to breakage during charging and discharging, and the formation of new surfaces is suppressed. As a result, the micronization of the silicon-containing material at the end of the cycle is suppressed, and the consumption of the S-containing cyclic compound component used to form the film at the negative electrode can be reduced. As a result, the S-containing cyclic compound component can play an effective role in the positive electrode, thus maintaining high cycle characteristics for a long time and achieving a long-life non-aqueous electrolyte secondary battery.

[0040] On the other hand, if the porosity of silicon-containing materials exceeds 20%, it becomes difficult to ensure high capacity, and the current collection performance decreases. Furthermore, the particle strength of silicon-containing materials themselves decreases. Therefore, it is difficult to provide non-aqueous electrolyte secondary batteries with excellent cycle characteristics.

[0041] The internal porosity of a particle refers to the ratio (%) of the area SC2 of the internal voids G1 in the cross-section of the negative electrode active material particle to the area SC1 of the negative electrode active material particle, calculated as (SC2 / SC1) × 100. The area SC1 of the negative electrode active material particle refers to the area enclosed by the outline of the particle, obtained by adding the area occupied by the negative electrode active material to the area of ​​the internal voids G1 enclosed by that outline. In the case of multiple internal voids G1, the area SC2 of the internal voids G1 refers to the total area of ​​all internal voids G1. The internal porosity of the particle is determined from the cross-sectional image of the layer containing the negative electrode active material (negative electrode mixture layer) using the following method.

[0042] First, the discharged secondary battery is disassembled to remove the negative electrode. Next, the negative electrode is cleaned with an organic solvent (such as anhydrous methyl ethyl carbonate or dimethyl carbonate), and then further vacuum dried to peel off only the negative electrode binder layer, thus obtaining a sample. Next, the cross-section of the negative electrode binder layer is exposed. As a method to expose the cross-section, for example, a portion of the negative electrode can be cut and processed using an ion milling device (e.g., Hitachi High-Tech IM4000PLUS) to obtain the cross-section of the negative electrode binder layer.

[0043] Next, a backscattered electron image of the exposed negative electrode mixture layer is captured using a scanning electron microscope. The magnification for capturing the backscattered electron image is, for example, 3000–5000x. Particles containing silicon are selected from the cross-sectional image, and the boundaries of these particles are determined. Graphite is sometimes used in conjunction with silicon-containing materials as the negative electrode active material, but the brightness of the backscattered electron images of silicon-containing materials and graphite materials differs, thus allowing for differentiation. Alternatively, the ratio of the area of ​​silicon-containing material to the area of ​​graphite material in the cross-section of the negative electrode can be considered as a volume ratio, and the content of silicon-containing material can be calculated from these area ratios and the specific gravities of silicon-containing material and graphite material.

[0044] The obtained image is processed by binarization, where the cross-sectional area of ​​the silicon-containing material particles in the cross-sectional image is black, and the voids within the particles are white. In the binarization process, in the cross-sectional image, black represents the silicon-containing material particles (including internal voids), and white represents the voids between the particles.

[0045] Using a binarized cross-sectional image, arbitrarily select silicon-containing material particles with a maximum diameter of 5 μm or more but less than 50 μm, and calculate the area SC1 and the area SC2 of the internal voids. It should be noted that in image analysis, it is sometimes difficult to determine whether tiny voids with a maximum diameter of less than 3 μm are internal or external voids. Therefore, voids with a maximum diameter of less than 3 μm are considered internal voids.

[0046] Using the particle area SC1 and internal void area SC2 of the silicon-containing material obtained above, the particle internal porosity (%) shown in the above formula is calculated for more than 10 silicon-containing material particles, and the average value is taken as the particle internal porosity of the silicon-containing material. For example, ImageJ, manufactured by the National Institutes of Health, can be used as image analysis software for image processing.

[0047] The average pore size of silicon-containing materials can also be calculated based on the shape of the internal voids G1. Specifically, the diameter (equivalent diameter) of a circle with an area equal to the area of ​​the internal voids G1 is determined. Within a particle of silicon-containing material (more than 10 particles), the equivalent diameter of each void G1 is calculated, and their average value is taken as the average pore size of the silicon-containing material. The average pore size calculated in this way is approximately consistent with the average pore size measured in silicon-containing material powder before it is used to construct a secondary battery.

[0048] There are no particular limitations on the method for controlling the internal porosity of silicon-containing materials or carbon composite particles. For example, the porosity can be controlled in a way that achieves the desired particle porosity through the manufacturing process of the silicon-containing material. Examples of such methods include the selection of materials constituting the ion-conducting phase and applying pressure while heating the silicon-containing material before pulverization. The heating temperature can be, for example, 300°C to 800°C. For example, when the material used to form the ion-conducting phase contains substances that can be removed by heating, there is a tendency that the greater the amount of heat-removable substances, the more voids are formed within the ion-conducting phase, resulting in a higher particle porosity, and a larger specific surface area and / or average pore size.

[0049] Carbon composite particles can be obtained, for example, by mixing a carbon source with silicon, simultaneously crushing and stirring the mixture using a mixer such as a ball mill, and then calcining the mixture in an inactive atmosphere. As a carbon source, for example, pitch, tar, sugars, water-soluble resins, etc., can be used. Pitch, carboxymethyl cellulose (CMC), polyvinylpyrrolidone, cellulose, sucrose, etc., are preferred. When mixing the carbon source and silicon, for example, the carbon source and silicon can be dispersed in a dispersion medium such as an alcohol.

[0050] A pore-forming agent can be mixed into the mixture of carbon source and raw silicon. By removing the pore-forming agent from the calcined product, the carbon composite particles can be made porous. The porosity within the carbon composite particles can be controlled by varying the amount of pore-forming agent mixed in. The pore-forming agent is not particularly limited; for example, a powder that readily dissolves in an acidic aqueous solution that is almost insoluble in the silicon phase can be used. Examples of such powdered pore-forming agents include oxides of transition metals (e.g., Cu, Fe). The median particle size in the volumetric particle size distribution of the pore-forming agent is appropriately selected based on the desired fine pore size distribution of the carbon composite particles. The acid used in the acidic aqueous solution can be dilute sulfuric acid, etc.

[0051] The silicon-containing material content relative to the overall negative electrode active material is, for example, 0.5% by mass or more, or even 1% by mass or more, 2% by mass or more, 3% by mass or more, 4% by mass or more, or 5% by mass or more. When the silicon-containing material content is within this range, the volume changes accompanying lithium ion uptake and release can easily lead to side reactions at the nascent surface. Therefore, the effects of using a non-aqueous electrolyte containing S-cyclic compounds are readily and significantly demonstrated. From the viewpoint of ensuring higher cycle performance, the silicon-containing material content in the negative electrode active material is, for example, 20% by mass or less, or even 10% by mass or less.

[0052] Figure 1This is a longitudinal cross-sectional view schematically illustrating the discharge state of a non-aqueous electrolyte secondary battery of this embodiment, comprising carbon composite particles as a silicon-containing negative electrode (negative electrode flux layer). The carbon composite particles 30 are porous and consist of a carbon phase 301 and a silicon phase 302. The silicon phase 302 exists dispersed within the carbon phase 301. Internal voids 303 exist near the silicon phase 302. Interparticle voids 33 are formed between the carbon composite particles 30 and other particles. A portion of the interparticle voids 33 is an external void 34 surrounded by the inner wall of the carbon composite particles 30 but communicating with the interparticle voids 33.

[0053] It should be noted that, in Figure 1 In this context, particles other than those shown as carbon composite particles 30 are not particularly limited; they can be carbon composite particles, carbon material particles such as graphite particles, or silicon-containing material particles other than carbon composite particles.

[0054] In the discharged state, the silicon phase (here, since it is represented in particle form, it is also called "silicon particles") has a small volume and exists in a state with a large number of internal voids 303. On the other hand, in the charged state, the silicon particles expand, thereby increasing the volume of the silicon phase. However, since the internal voids 303 are kept sufficiently spacious, the expansion of the carbon composite particles 30 themselves is suppressed. In addition, when the silicon phase 302 contracts, the volume of the originally existing internal voids 303 is restored, thereby maintaining the interparticle junctions within the negative electrode binder layer.

[0055] Furthermore, the carbon composite particles 30 can retain a considerable amount of non-aqueous electrolyte (i.e., lithium ions) within their internal voids 303. Therefore, they can receive lithium ions from both the internal voids 303 and the interparticle voids 33. Consequently, the lithium ion supply to the carbon composite particles 30, which require a large amount of lithium ions during charging, is less likely to be interrupted.

[0056] The following describes in more detail an example of the configuration of the non-aqueous electrolyte secondary battery of this disclosure. Besides using the aforementioned silicon-containing material as the negative electrode active material and the aforementioned non-aqueous electrolyte containing the aforementioned S-cyclic compound component, various other constituent elements can be selected. For example, known constituent elements can be used for other components besides the negative electrode active material. The secondary battery of this disclosure typically includes a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive and negative electrodes. These constituent elements will be described below.

[0057] (negative electrode)

[0058] The negative electrode contains a negative electrode binder. The negative electrode may contain a negative electrode binder and a negative electrode current collector that retains the negative electrode binder. The negative electrode typically has a layered negative electrode binder (hereinafter referred to as a negative electrode binder layer). The negative electrode binder contains at least a negative electrode active material. The negative electrode binder may further contain at least one selected from binders and thickeners. The negative electrode binder may further contain conductive agents, etc.

[0059] (Negative electrode mixture)

[0060] (Negative electrode active material)

[0061] The negative electrode active material must contain at least a Si-containing material. The negative electrode may also contain materials other than Si-containing materials as the negative electrode active material. The Si-containing material may include carbon composite particles.

[0062] (Including Si materials)

[0063] In Si-containing materials, carbon composite particles consist of a carbon phase and a Si phase dispersed within the carbon phase. Because the carbon phase is electronically conductive, even if cracks form within the carbon composite particles due to the expansion and contraction of the Si phase, they are not easily isolated, and the junctions between the carbon composite particles and their surroundings are easily maintained. Therefore, it is easier to suppress the degradation of cycling characteristics.

[0064] The carbon phase can be composed of amorphous carbon (i.e., non-crystalline carbon) or crystalline carbon. Amorphous carbon can be hard carbon, soft carbon, or other types of carbon. Amorphous carbon generally refers to carbonaceous materials whose average interplanar spacing d002 of the (002) plane, as determined by X-ray diffraction, exceeds 0.340 nm. Examples of crystalline carbon include graphite and other carbons with a graphite-type crystal structure. Crystalline carbon, such as graphite, refers to carbonaceous materials with d002 of 0.340 nm or less (e.g., 0.3354 nm or more and 0.340 nm or less).

[0065] The Si phase content in the carbon composite particles can be, for example, 30% by mass or more and 80% by mass or less, or 40% by mass or more and 70% by mass or less. Within this range, higher initial capacity can be obtained, and the reduction in cycle performance can be easily mitigated. Furthermore, by including a larger amount of carbon phase, even if cracks form in the particles due to charge and discharge, the carbon phase can easily penetrate the resulting voids, thus maintaining the conductive pathway in the negative electrode composite.

[0066] The content of carbon composite particles in the negative electrode active material can be, for example, 2% by mass or more, 3% by mass or more, 4% by mass or more, or 5% by mass or more. When the content of carbon composite particles is within this range, the volume changes accompanying lithium ion uptake and release can easily lead to the effects of side reactions on the nascent surface. Therefore, the effects of using a non-aqueous electrolyte containing S-cyclic compounds are readily and significantly demonstrated. From the viewpoint of ensuring higher cycle performance, the content of carbon composite particles in the negative electrode active material can be, for example, 20% by mass or less, or even 10% by mass or less.

[0067] Carbon composite particles can be obtained, for example, by pulverizing a mixture of a carbon source and raw silicon using a ball mill or similar device while stirring, followed by heat treatment of the mixture in an inert atmosphere. Examples of carbon sources that can be used include petroleum resins such as coal tar pitch, petroleum pitch, and petroleum tar, carboxymethyl cellulose (CMC), polyvinylpyrrolidone, cellulose, sugars such as sucrose, and water-soluble resins. When mixing the carbon source and raw silicon, they can be dispersed in a dispersion medium such as an alcohol. After drying the milled mixture, it is heated in an inert gas atmosphere, for example, at a temperature above 600°C and below 1000°C, to carbonize the carbon source, thereby forming a carbon phase.

[0068] Other examples of Si-containing materials besides carbon composite particles include elemental silicon, silicon alloys, and silicon compounds.

[0069] Si-containing materials can contain composite particles other than carbon composite particles. Examples of such composite particles include those in which a Si phase (fine Si phase) is dispersed within the lithium-ion conducting phase (matrix). When a Si-containing material contains such composite particles, higher capacity can be achieved, and the effect of suppressing cycling performance degradation can be improved.

[0070] The lithium-ion conducting phase preferably comprises at least one phase selected from SiO2 and silicate phases. The lithium-ion conducting phase may further comprise a carbon phase. The lithium-ion conducting phase can form an amorphous phase. However, it is not limited to this; for example, at least a portion of each of the silicate phase and the carbon phase may also be a crystalline phase comprising crystalline silicate or crystalline carbon as described for carbon composite particles. Specific examples of composite particles include composite particles comprising a SiO2 phase and a Si phase dispersed within the SiO2 phase, and composite particles comprising a silicate phase and a Si phase dispersed within the silicate phase (silicate composite particles). However, the composite particles are not limited to these specific examples.

[0071] The SiO2 phase is an amorphous phase containing more than 95% by mass of silicon dioxide. Composite particles containing Si phase dispersed within the SiO2 phase are used in SiO2 composites. xThis indicates that x is, for example, 0.5 ≤ x < 2, or 0.8 ≤ x ≤ 1.6. SiO x For example, it can be obtained by heat-treating silicon monoxide, using a disproportionation reaction to separate it into the SiO2 phase and a fine Si phase. If SiO2 is observed using a transmission electron microscope (TEM), it can be further analyzed. x By examining the particle cross-section, the Si phase dispersed within the SiO2 phase can be identified. In this specification, such composite particles are sometimes referred to as silicon oxide. When the negative electrode active material contains silicon oxide, it is easier to ensure a higher initial discharge capacity.

[0072] The preferred silicate phase comprises at least one alkali metal element (Group 1 elements excluding hydrogen in the long-period periodic table) and a Group 2 element in the long-period periodic table. Alkali metal elements include lithium (Li), potassium (K), sodium (Na), etc. Group 2 elements include magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), etc. The lithium silicate phase can have the formula: Li 2y SiO 2+y The composition shown is (0 < y < 2). y can be 1 / 2 or 1. Silicate composite particles with the Si phase dispersed in the silicate phase can be obtained, for example, by micronizing a mixture of silicate and raw silicon by stirring and pulverizing it in a ball mill or similar device, and then heat-treating the mixture in an inactive atmosphere.

[0073] Compared to the silicate composite particles as a whole, the content of the Si phase dispersed within the silicate phase can be above 30% by mass and below 95% by mass, or above 35% by mass and below 75% by mass.

[0074] Si-containing materials may contain only carbon composite particles, or they may combine at least one selected from other Si-containing materials with carbon composite particles. For example, in addition to carbon composite particles, Si-containing materials may also contain at least one selected from silicon oxide and silicate composite particles.

[0075] The content of silicon oxide in the negative electrode active material is, for example, 0.1% by mass or more, or 0.5% by mass or more, or 1% by mass or more. In this case, the initial discharge capacity can be further improved. The content of silicon oxide in the negative electrode active material is, for example, 20% by mass or less, or 10% by mass or less, or 5% by mass or less.

[0076] The content of silicate composite particles in the negative electrode active material is, for example, 0.1% by mass or more, or 0.5% by mass or more, or 1% by mass or more. In this case, a higher initial discharge capacity can be ensured, and the decrease in capacity retention rate can be further suppressed. The content of silicate composite particles in the negative electrode active material is, for example, 20% by mass or less, or 10% by mass or less, or 5% by mass or less.

[0077] The composition of Si-containing materials can be determined, for example, by obtaining a backscattered electron image of the cross-section of the negative electrode binder layer using a field emission scanning electron microscope (FE-SEM), observing the Si-containing material particles, and performing elemental analysis on the observed Si-containing material particles. For instance, the battery can be disassembled, the negative electrode removed, cleaned with a non-aqueous solvent such as ethylene carbonate, dried, and then the cross-section of the negative electrode binder layer can be processed using a cross-section polisher (CP) to obtain a sample. A backscattered electron image of the sample cross-section can be taken using FE-SEM. Elemental analysis can be performed using an electron probe microanalyzer (EPMA). Qualitative and quantitative elemental analysis can also be performed using Auger electron spectroscopy (AES). Through the above analysis, the composition of the lithium-ion conducting phase can also be determined. The composition of the carbon phase can be confirmed based on d002 determined by X-ray diffraction.

[0078] Si-containing materials are typically in particulate form. The average particle size (D50) of Si-containing materials is, for example, greater than 1 μm and less than 25 μm, or greater than 4 μm and less than 15 μm. Good battery performance is easily obtained within these ranges.

[0079] It should be noted that in this specification, the average particle size (D50) refers to the particle size that accounts for 50% of the total volume in the particle size distribution determined by laser diffraction scattering (volume average particle size). The measuring apparatus can be, for example, the "LA-750" manufactured by Horiba Corporation. The average particle size of the Si-containing material can be determined from the cross-sectional sample of the negative electrode formed to obtain a backscattered electron image for FE-SEM. The equivalent circle diameters of the cross-sections of 10 or more Si-containing material particles are determined, and their average value is taken as the average particle size. Here, the equivalent circle diameter refers to the diameter of a circle having an area equal to the area of ​​the particles observed in the cross-section of the negative electrode.

[0080] The Si phase dispersed within the carbon phase typically consists of multiple crystallites. The crystallite size of the Si phase can be, for example, less than 500 nm, or less than 30 nm. There is no particular lower limit to the crystallite size of the Si phase, for example, it can be greater than 5 nm. The crystallite size can be calculated using the Scherrer formula based on the half-width of the diffraction peaks attributable to the Si (111) plane in the X-ray diffraction (XRD) pattern of the Si phase.

[0081] The content of the Si phase in the composite particles can be determined, for example, by Si-NMR. Preferred measurement conditions for Si-NMR are shown below.

[0082] Measurement apparatus: Varian Corporation, solid-state nuclear magnetic resonance spectroscopy apparatus (INOVA-400)

[0083] Probe: Varian 7mm CPMAS-2

[0084] MAS: 4.2kHz

[0085] MAS speed: 4kHz

[0086] Pulse: DD (45° pulse + 1H signal acquisition time for decoupling)

[0087] Repeat time: 1200 sec

[0088] Observation width: 100kHz

[0089] Observation center: around -100ppm

[0090] Signal acquisition time: 0.05 sec

[0091] Total number of times: 560

[0092] Sample volume: 207.6 mg

[0093] From the viewpoint of improving conductivity, at least a portion of the surface of Si-containing material particles can be coated with a conductive layer. The conductive layer comprises a conductive material such as conductive carbon. The amount of conductive layer coating is, for example, more than 1 part by mass and less than 10 parts by mass relative to 100 parts by mass of the total Si-containing material particles and conductive layer. The Si-containing material particles with the conductive layer on their surface are obtained, for example, by mixing Si-containing material particles with a mixture of coal tar pitch and performing heat treatment in an inactive atmosphere.

[0094] The content of Si-containing material in the negative electrode active material is 3% by mass or more, preferably 4% by mass or more, and can be 5% by mass or more. While high initial capacity can be obtained at such a content range, cycling characteristics tend to decrease. In this disclosure, even under such conditions, high cycling characteristics can be ensured by using a non-aqueous electrolyte containing a component of an S-cyclic compound. The proportion of Si-containing material is, for example, 15% by mass or less, and can also be 10% by mass or less. These lower and upper limits can be combined arbitrarily.

[0095] (Other negative electrode active materials)

[0096] Examples of anode active materials other than Si-containing materials include at least one selected from Si-free carbonaceous materials, elemental Sn, Sn alloys, and Sn compounds (such as Sn oxides). Si-containing materials expand and contract in volume during charge and discharge; therefore, if their proportion in the anode active material increases, poor contact between the anode active material and the anode current collector is more likely to occur during charge and discharge. Carbonaceous materials, compared to Si-containing materials, exhibit less expansion and contraction during charge and discharge. By combining Si-containing and carbonaceous materials, the contact state between the anode active material particles and between the anode current collector and the anode current collector can be maintained better under repeated charge and discharge conditions. Therefore, by combining Si-containing materials and Si-free carbonaceous materials, excellent cycle characteristics can be easily obtained while imparting high capacity to the anode with the Si phase.

[0097] Examples of carbonaceous materials include graphite, easily graphitized carbon (soft carbon), and difficult-to-graphitize carbon (hard carbon). A single carbonaceous material can be used alone, or two or more can be used in combination.

[0098] From the perspectives of excellent charge-discharge stability and low irreversible capacity, graphite is particularly preferred as a carbonaceous material. Examples of graphite include natural graphite, artificial graphite, and graphitized mesophase carbon particles. Graphite particles can partially comprise amorphous carbon, easily graphitized carbon, and difficult-to-graphitize carbon.

[0099] Graphite is a carbonaceous material with a well-developed graphitic crystal structure. The average interplanar spacing d002 of the (002) facets of graphite, as determined by X-ray diffraction, can be, for example, 0.340 nm or less, or 0.3354 nm or more but less than 0.340 nm. Furthermore, the crystallite size Lc(002) of graphite can be, for example, 5 nm or more, or 5 nm or more but less than 200 nm. The crystallite size Lc(002) is determined, for example, by the Scherrer method. When the average interplanar spacing d002 of the (002) facets of graphite and the crystallite size Lc(002) are within the above-mentioned ranges, high capacity is easily obtained.

[0100] The total amount of Si-containing materials and carbonaceous materials (carbonaceous materials without the Si phase) in the negative electrode active material is preferably 90% by mass or more, or it can be 95% by mass or more, or 98% by mass or more. The total amount of Si-containing materials and carbonaceous materials in the negative electrode active material is less than 100% by mass. The negative electrode active material can be composed solely of Si-containing materials and carbonaceous materials.

[0101] (Adhesive)

[0102] As an adhesive, resin materials can be used, for example. Examples of adhesives include fluoropolymers (e.g., polytetrafluoroethylene, polyvinylidene fluoride), polyolefin resins (e.g., polyethylene, polypropylene), polyamide resins (e.g., aromatic polyamide resins), polyimide resins (e.g., polyimide, polyamide-imide), acrylic resins (e.g., polyacrylic acid, polymethacrylic acid, acrylic-methacrylic acid copolymer, ethylene-acrylic acid copolymer, or their salts), vinyl resins (e.g., polyvinyl acetate), and rubber-like materials (e.g., styrene-butadiene copolymer rubber (SBR)). One adhesive can be used alone, or two or more can be used in combination.

[0103] (Thickener)

[0104] Examples of thickeners include cellulose derivatives such as cellulose ethers. Examples of cellulose derivatives include CMC and its modified forms, methylcellulose, etc. Modified forms of CMC also include CMC salts. Examples of salts include alkali metal salts (e.g., sodium salts), ammonium salts, etc. Thickeners can be used alone or in combination of two or more.

[0105] (Conductive agent)

[0106] Examples of conductive agents include conductive fibers and conductive particles. Examples of conductive fibers include carbon fibers and metal fibers. Carbon fibers also include carbon nanotubes (CNTs). Examples of conductive particles include conductive carbon (carbon black, etc.) and metal powders. A single conductive agent can be used, or two or more can be used in combination.

[0107] Si-containing materials exhibit significant volume changes due to expansion and contraction during charging and discharging. When the negative electrode additive contains CNTs, even if particle breakage occurs due to the expansion and contraction of the Si-containing material, the interruption of the conductive path is suppressed by the CNTs, making it easier to obtain higher cycle performance. In particular, when the content of Si-containing material in the negative electrode active material is high (e.g., 4% by mass or more), the effect brought by CNTs is significantly manifested.

[0108] CNTs are carbonaceous materials with a diameter of nanometers, possessing a structure in which sheets (graphene) forming a six-membered ring network of carbon atoms are rolled into a cylindrical shape. CNTs exhibit excellent electrical conductivity. When the number of graphene layers constituting the cylindrical structure is one, it is called a single-walled CNT (SWCNT). When the number of layers is multiple, it is called a multi-walled CNT (MWCNT).

[0109] CNTs preferably include SWCNTs. In this case, it is easy to ensure higher cycle performance.

[0110] The proportion of SWCNTs in CNTs can be, for example, over 50%, over 75%, or even over 90%. The proportion of SWCNTs in CNTs is less than 100%. It should be noted that the proportion of SWCNTs in CNTs refers to the ratio of the number of SWCNTs to the total number of CNTs.

[0111] The presence of CNTs in the negative electrode mixture can be confirmed, for example, by scanning electron microscopy (SEM) images of the cross-section of the negative electrode mixture layer.

[0112] The proportion of SWCNT in the CNT contained in the negative electrode mixture was determined by the following method.

[0113] Use SEM to obtain cross-sectional images of the negative electrode compound layer or CNTs. In the SEM images, randomly select multiple CNTs (e.g., more than 50 and less than 200) for observation, determine the number of SWCNTs, and calculate the ratio of the number of SWCNTs to the total number of selected CNTs.

[0114] Quantitative analysis of CNTs can be performed, for example, by combining Raman spectroscopy and thermogravimetric analysis.

[0115] From the perspective of reducing the interruption of conductive paths during charging and discharging, the average diameter of CNTs can be, for example, 1 nm or more and 10 nm or less, or 1 nm or more and 5 nm or less.

[0116] From the viewpoint of reducing the interruption of conductive paths during charging and discharging, the average length of CNTs can be, for example, 1 μm or more and 100 μm or less, or 5 μm or more and 20 μm or less.

[0117] The average length and average diameter of CNTs can be determined using at least one of SEM and TEM images, either from a cross-section of the negative electrode composite layer or from an image of the CNTs. More specifically, multiple CNTs (e.g., more than 50 but less than 200) are randomly selected from the captured images, their lengths and diameters are measured, and then averaged to determine the average length and average diameter. It should be noted that the length of a CNT refers to its length when stretched into a straight line.

[0118] The CNT content in the negative electrode additive is, for example, 0.005% by mass or more and 1% by mass or less, or 0.01% by mass or more and 1% by mass or less, or 0.01% by mass or more and 0.05% by mass or less. When the CNT content in the negative electrode additive is within such a range, the effect of improving the conductivity of the negative electrode and the improvement of the capacity retention rate at the beginning of charge-discharge cycles is greater.

[0119] (Negative current collector)

[0120] The negative electrode current collector is selected based on the type of non-aqueous electrolyte secondary battery. Examples of negative electrode current collectors include sheet-shaped current collectors. Metal foils can also be used. Alternatively, porous current collectors can be used. Examples of porous current collectors include meshes, perforated sheets, and expanded metal.

[0121] Examples of materials that can be used as negative current collectors include stainless steel, nickel, nickel alloys, copper, and copper alloys.

[0122] There is no particular limitation on the thickness of the negative current collector; for example, it can be 1 μm or more and 50 μm or less, or it can be 5 μm or more and 30 μm or less.

[0123] (other)

[0124] The negative electrode can be formed, for example, by coating a negative electrode slurry, which disperses the components of the negative electrode compound in a dispersion medium, onto the surface of the negative electrode current collector and then drying it. The dried coating can be calendered as needed.

[0125] There are no particular limitations on the dispersion medium, for example water, alcohols (e.g., ethanol), ethers (e.g., tetrahydrofuran), amides (e.g., dimethylformamide), N-methyl-2-pyrrolidone (NMP), or mixtures thereof.

[0126] (positive electrode)

[0127] The positive electrode may have a positive current collector and a positive electrode additive layer maintained on the surface of the positive current collector. The positive electrode additive layer is formed by coating a positive electrode slurry, in which the positive electrode additive is dispersed in a dispersion medium, onto the surface of the positive current collector and allowing it to dry. The dried coating film may be calendered as needed. The positive electrode additive contains a positive electrode active material as an essential component and may contain binders, conductive agents, etc., as arbitrary components. As the dispersion medium, for example, it may be selected from the dispersion medium exemplified for the negative electrode.

[0128] As a positive electrode active material, a composite oxide containing lithium and a transition metal can be used, for example. Examples of transition metals include Ni, Co, and Mn. Examples of composite oxides containing lithium and a transition metal include Li. a CoO2, Li a NiO2, Li a MnO2, Li a Co b1 Ni 1-b1 O2, Li a Co b1 M 1-b1 O c1 Li a Ni 1-b1 M b1 O c1 Li a Mn2O4, Li a Mn 2-b1 M b1 O4. Here, a = 0–1.2, b1 = 0–0.9, c1 = 2.0–2.3. M is at least one selected from Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B. It should be noted that the value of a, representing the molar ratio of lithium, increases or decreases due to charging and discharging.

[0129] Li is preferred. a Ni b2 M 1-b2 Lithium-nickel composite oxides are shown as O2 (0 < a ≤ 1.2, 0.3 ≤ b2 ≤ 1, and M is at least one selected from Mn, Co, and Al). From the viewpoint of high capacity, it is more preferable to satisfy 0.8 ≤ b2 ≤ 1 or 0.85 ≤ b2 ≤ 1. From the viewpoint of crystal structure stability, Li is even more preferable. a Ni b2 Co c2 Al d O2 (0 < a ≤ 1.2, 0.8 ≤ b2 < 1, 0 < c2 < 0.2 (or 0 < c2 ≤ 0.18), 0 < d ≤ 0.1, b2 + c2 + d = 1).

[0130] As a binder, resin materials exemplified in the negative electrode can be used. As a conductive agent, for example, conductive agents exemplified in the negative electrode can be selected. Graphite can be used as a conductive agent.

[0131] The shape and thickness of the positive current collector can be selected from the shape and range described for the negative current collector. Examples of materials that can be used for the positive current collector include stainless steel, aluminum, aluminum alloys, and titanium.

[0132] (Diaphragm)

[0133] A separator is typically sandwiched between the positive and negative electrodes. The separator has high ion permeability and possesses moderate mechanical strength and insulation. Examples of separators include microporous membranes, woven fabrics, and nonwoven fabrics. The separator can be a single-layer or multi-layer structure. A multi-layer separator can be a laminate comprising at least two layers selected from microporous membranes, woven fabrics, and nonwoven fabrics. Polyolefins (e.g., polypropylene, polyethylene) are preferred as the separator material.

[0134] (Non-aqueous electrolyte)

[0135] Non-aqueous electrolytes are typically used in a liquid state, but can also be used in a state where flowability is restricted, such as with a gelling agent. Non-aqueous electrolytes typically contain a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent, as well as additives. In this disclosure, the non-aqueous electrolyte contains an S-cyclic compound component. The non-aqueous electrolyte may further contain additives other than the S-cyclic compound component.

[0136] (Non-aqueous solvent)

[0137] Examples of non-aqueous solvents include cyclic carbonates, chain carbonates, cyclic carboxylic acid esters, and chain carboxylic acid esters. Examples of cyclic carbonates include propylene carbonate (PC), ethylene carbonate (EC), fluoroethylene carbonate (FEC), and vinylene carbonate (VC). Examples of chain carbonates include diethyl carbonate (DEC), methyl ethyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of cyclic carboxylic acid esters include γ-butyrolactone (GBL) and γ-valerolactone (GVL). Examples of chain carboxylic acid esters include methyl formate, ethyl formate, propyl formate, methyl acetate (MA), ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, and propyl propionate. Non-aqueous electrolytes may contain one non-aqueous solvent or a combination of two or more.

[0138] (Lithium salt)

[0139] Examples of lithium salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, and LiB.10 Cl 10 Examples of lithium salts include lower aliphatic carboxylic acids such as lithium Cl, LiBr, LiI, phosphates, borates, and imide salts. Examples of phosphates include lithium difluorophosphate (LiPO₂F₂), lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium tetrafluoro(oxalate)phosphate. Examples of borates include lithium bis(oxalate)borate (LiBOB) and lithium difluoro(oxalate)borate (LiDFOB). Examples of imide salts include lithium difluorosulfonylimide (LiN(FSO₂)₂), lithium bis(trifluoromethanesulfonylimide) (LiN(CF₃SO₂)₂), lithium trifluoromethanesulfonate nonafluorobutanesulfonylimide (LiN(CF₃SO₂)(C₄F₉SO₂)), and lithium bis(pentafluoroethanesulfonylimide) (LiN(C₂F₅SO₂)₂). Non-aqueous electrolytes may contain one type of lithium salt or a combination of two or more types.

[0140] The concentration of lithium salt in the electrolyte is, for example, above 0.5 mol / L and below 2 mol / L.

[0141] (Contains S-cyclic compound components)

[0142] An S-containing cyclic compound is a cyclic compound that contains sulfur (S) as a constituent element of the ring. In addition to the sulfur element constituting the ring, the cyclic compound may also contain oxygen. For example, an S-containing cyclic compound may contain an oxygen atom as a constituent element of the ring, or it may contain an oxo group (=O) that bonds to the ring as a substituent, or both. The oxo group may bond to the carbon element constituting the ring, but preferably to the sulfur element constituting the ring.

[0143] Such S-containing cyclic compounds can be, for example, at least one selected from sulfate esters, sulfites, and sulfonates. Sulfates have a -O-S(=O)₂-O⁻ structure. Sulfites have a -O-S(=O)⁻O⁻ structure. Sulfonates have a -S(=O)₂-O⁻ structure. Cyclic compounds also include salts of these esters. Among these, cyclic sulfites and cyclic sulfonates are preferred.

[0144] Examples of cyclic sulfates include alkylene sulfates and alkenyl sulfates. Specific examples of cyclic sulfates include ethylene sulfate, propylene sulfate, trimethylol sulfate, butyl sulfate, and vinylene sulfate. Examples of cyclic sulfites include at least one selected from alkylene sulfates and alkenyl sulfates. Specific examples of cyclic sulfites include ethylene sulfate, propylene sulfate, trimethylol sulfate, butyl sulfate, and vinylene sulfate. Examples of cyclic sulfonates include at least one selected from alkyl sulfonyl lactones and olefin sulfonyl lactones. Specific examples of cyclic sulfonates include 1,3-propane sulfonyl lactone, 1,4-butane sulfonyl lactone, and 1,3-propene sulfonyl lactone.

[0145] In S-ring compounds, one or more hydrogen atoms in the compounds exemplified above may be substituted with substituents. Examples of substituents include alkyl, alkenyl, hydroxyalkyl, hydroxyl, alkoxy, and halogen atoms. The number of carbon atoms in the substituent may be 1 or more and 4 or less, or 1 or more and 3 or less. Examples of halogen atoms include chlorine and fluorine atoms.

[0146] The S-containing rings in S-ring compounds are usually 5- or 6-membered.

[0147] The S-ring compound component may include one such S-ring compound, or it may include two or more in combination. The S-ring compound component preferably includes an S-ring compound having a carbon-carbon unsaturated bond. The carbon-carbon unsaturated bond may form part of the S-ring or may be included by a substituent containing the S-ring. Examples of such substituents include vinyl, allyl, and other alkenyl (C... 2-4 (Alkenyl groups, etc.). Specific examples of such S-cyclic compounds include 1,3-propenesulfonyl lactone, vinylene sulfite, vinyl ethylene sulfite, and vinylene sulfate. When the S-cyclic compound component includes at least 1,3-propenesulfonyl lactone, a high-quality coating readily forms on the surface of the negative electrode active material particles, including the nascent surface, resulting in higher cycling characteristics. The S-cyclic compound component may include 1,3-propenesulfonyl lactone and other S-cyclic compounds.

[0148] In the non-aqueous electrolyte secondary battery, the concentration of the S-containing cyclic compound component in the non-aqueous electrolyte is, for example, 2 mass% or less, and may be 1 mass% or less. This concentration of the S-containing cyclic compound component is a value determined for the non-aqueous electrolyte collected from the initial non-aqueous electrolyte secondary battery. In the non-aqueous electrolyte secondary battery, since the S-containing cyclic compound component is used for film formation, the concentration of the S-containing cyclic compound component in the non-aqueous electrolyte changes during storage or during charge-discharge cycles. Therefore, it is sufficient that the S-containing cyclic compound component remains at a concentration above the detection limit in the non-aqueous electrolyte collected from the initial non-aqueous electrolyte secondary battery. The content of the S-containing cyclic compound component in the electrolytic solution may be 0.1 mass% or more, may be 0.25 mass% or more, and may further be 0.5 mass% or more. The concentration of 1,3-propene sultone may be within the above range.

[0149] The initial non-aqueous electrolyte secondary battery refers to, for example, a non-aqueous electrolyte secondary battery obtained by assembling a non-aqueous electrolyte secondary battery and performing pre-charge-discharge (conditioning charge-discharge) (and aging as necessary). A commercially available non-aqueous electrolyte secondary battery may also be used as the initial non-aqueous electrolyte secondary battery, from which the non-aqueous electrolyte is collected and subjected to analysis.

[0150] The concentration of the S-containing cyclic compound component in the non-aqueous electrolyte used in the production of the non-aqueous electrolyte secondary battery may be 0.1 mass% or more, may be 0.2 mass% or more or 0.25 mass% or more, and may further be 0.5 mass% or more. The content of the S-containing cyclic compound component in the electrolytic solution used in the production of the non-aqueous electrolyte secondary battery is, for example, 2 mass% or less. The concentration of 1,3-propene sultone may be within the above range.

[0151] (Others)

[0152] The non-aqueous electrolyte may contain additives other than the S-containing cyclic compound component. Examples of such additives include sulfur-containing compounds other than the aforementioned S-containing cyclic compound component, phosphorus-containing compounds, nitrogen-containing compounds, vinyl ethylene carbonate, FEC, and aromatic compounds (cyclohexylbenzene, fluorobenzene, etc.). Examples of the sulfur-containing compound (S-containing compound) include at least one selected from linear sulfates (diethyl sulfate, dimethyl sulfate, etc.), linear sulfites, and linear sulfonates. The S-containing compounds also include salts of these esters (diethyl sulfate salt, dimethyl sulfate salt, etc.). The non-aqueous electrolyte may contain one type of these additives, or may contain two or more types in combination.

[0153] Non-aqueous electrolyte secondary batteries preferably contain FEC. In this case, higher cycle characteristics are easily obtained. FEC can be contained in a small amount (e.g., more than 0.1% by mass and less than 2% by mass) as an additive, or in a larger amount (e.g., more than 2% by mass) as a non-aqueous solvent in the non-aqueous electrolyte.

[0154] (other)

[0155] As an example of the structure of a non-aqueous electrolyte secondary battery, one can exemplify a structure in which an electrode assembly, consisting of a positive and a negative electrode wound together with a separator, is housed together with the non-aqueous electrolyte in an outer casing. However, the structure of a non-aqueous electrolyte secondary battery is not limited to this structure. For example, the electrode assembly can also be a stacked type, where the positive and negative electrodes are layered together with a separator. The shape of the non-aqueous electrolyte secondary battery is also not limited; for example, it can be cylindrical, square, coin-shaped, button-shaped, or laminated.

[0156] Figure 2 This is a simplified perspective view showing a portion of a square non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure. The non-aqueous electrolyte secondary battery includes a square-bottomed battery casing 4 and an electrode assembly 1 and an electrolyte (not shown) housed within the battery casing 4. The electrode assembly 1 has a strip-shaped negative electrode, a strip-shaped positive electrode, and a separator between them. The negative electrode current collector is electrically connected to a negative terminal 6 disposed on a sealing plate 5 via a negative electrode lead 3. The negative terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. The positive electrode current collector is electrically connected to the back side of the sealing plate 5 via a positive electrode lead 2. That is, the positive electrode is electrically connected to the battery casing 4, which also serves as the positive terminal. The periphery of the sealing plate 5 is fitted into the open end of the battery casing 4, and the fitting portion is laser-welded. The sealing plate 5 has an electrolyte injection hole, which is blocked by a sealing plug 8 after electrolyte injection.

[0157] Postscript

[0158] The following technology has been disclosed through the above description of the embodiments.

[0159] (Technology 1)

[0160] A non-aqueous electrolyte secondary battery comprises: a negative electrode containing a negative electrode mixture, a separator, a positive electrode separated from the negative electrode by the separator, and a non-aqueous electrolyte.

[0161] The aforementioned negative electrode mixture contains negative electrode active substances.

[0162] The aforementioned negative electrode active material includes silicon-containing materials.

[0163] The porosity of the particles in the aforementioned silicon-containing materials is between 6% and 20%.

[0164] The aforementioned non-aqueous electrolyte contains a 5- or 6-membered cyclic compound component at a concentration of 0.1 to 2% by mass, wherein the 5- or 6-membered cyclic compound component contains sulfur as a constituent element of the ring.

[0165] (Technology 2)

[0166] According to the non-aqueous electrolyte secondary battery described in Technique 1, the silicon-containing material comprises carbon composite particles, wherein the carbon composite particles comprise a carbon phase and a silicon phase dispersed within the carbon phase.

[0167] (Technology 3)

[0168] According to the non-aqueous electrolyte secondary battery described in Technology 2, the specific surface area of ​​the aforementioned carbon composite particles is 5 m². 2 / g or more and 20m 2 / g or less.

[0169] (Technology 4)

[0170] According to the non-aqueous electrolyte secondary battery described in Technology 2 or 3, the average pore size of the aforementioned carbon composite particles is 1 nm or more and 45 nm or less.

[0171] (Technology 5)

[0172] According to any one of the non-aqueous electrolyte secondary batteries described in art 1 to 4, the cyclic compound component comprises a cyclic compound containing sulfur as a ring constituent element and having carbon-carbon unsaturated bonds.

[0173] (Technology 6)

[0174] According to any one of the non-aqueous electrolyte secondary batteries described in technology 1 to 5, the aforementioned cyclic compound component includes 1,3-propenyl sulfonyl lactone.

[0175] (Technology 7)

[0176] According to any one of the non-aqueous electrolyte secondary batteries described in technology 1 to 6, the content of the silicon-containing material relative to the overall content of the negative electrode active material is in the range of 0.5% to 20% by mass.

[0177] [Example]

[0178] The present invention will now be described in detail based on embodiments and comparative examples, but the present invention is not limited to the following embodiments.

[0179] Examples 1-3 and Comparative Examples 1-6

[0180] Construct a non-aqueous electrolyte secondary battery according to the following steps and then evaluate it.

[0181] (1) Fabrication of the negative electrode

[0182] Coal tar pitch as the carbon source and coarse particles of raw silicon (purity ≥ 99.9%, average particle size 100 nm) were mixed in a specified ratio. Iron oxide (FeO) was added as a pore-forming agent at a ratio of 5–30 parts by mass per 100 parts by mass of the mixture, and the mixture was further mixed. The mixture was then calcined at 600–1000 °C for 1–10 hours in a non-oxidizing atmosphere such as nitrogen or argon to obtain a blocky calcined product. The calcined product was pulverized using a ball mill to achieve the desired average particle size (median particle size). After washing with an acidic aqueous solution containing sulfuric acid, the product was dried to obtain carbon composite particles containing a carbon phase and a Si phase dispersed within the carbon phase. The average particle size (D50) of the carbon composite particles was 6 μm.

[0183] The porosity of the carbon composite particles is adjusted to a target value by regulating the proportion of iron oxide (FeO) in the mixture to be burned and / or the proportion of fixed carbon in the coal tar pitch. The lower the fixed carbon content in the pitch, the more components volatilize during carbonization upon heating, resulting in more internal porosity, a larger particle porosity, and consequently, a larger specific surface area and / or average pore size. Furthermore, a higher proportion of iron oxide results in more iron oxide being removed during washing with an acidic aqueous solution, further increasing the particle porosity, specific surface area, and / or average pore size.

[0184] The composition of the carbon composite particles was analyzed by ICP (inductively coupled plasma atomic emission spectrometry), and the result showed that the silicon content was 50.1% by mass.

[0185] As the negative electrode active material, graphite particles and carbon composite particles are mixed at a mass ratio of graphite particles:carbon composite particles = 95:5. The graphite particles used have an average particle size (D50) of 25 μm.

[0186] A negative electrode mixture is prepared by mixing the negative electrode active material, binder, and conductive agent. Adding an appropriate amount of water to the mixture yields the negative electrode slurry. The binders used are sodium polyacrylate (PAA-Na), sodium salt of CMC (CMC-Na), and SBR. The conductive agent used is CNT containing more than 90% SWCNT (average diameter approximately 1.6 nm, average length approximately 5 μm).

[0187] The CNT content in the negative electrode mixture (dried solids component) is set at 0.05% by mass. The contents of PAA-Na, CMC-Na, and SBR in the negative electrode mixture are each set at 1% by mass based on the dried solids component.

[0188] Next, a negative electrode slurry is coated onto the surface of the copper foil. After the coating dries, it is rolled to form a negative electrode mixture layer (80 μm thick, 1.6 g / cm³) on both sides of the copper foil. 3 ), thus obtaining the negative electrode.

[0189] (2) Production of the positive electrode

[0190] To lithium-containing composite oxides (LiNi) 0.8 Co 0.18 Al 0.02 To obtain the positive electrode slurry, 2.5 parts by weight of acetylene black, 2.5 parts by weight of polyvinylidene fluoride, and an appropriate amount of NMP were added to 95 parts by weight of O2. Next, the positive electrode slurry was coated onto the surface of aluminum foil. After the coating dried, it was calendered to form a positive electrode mixture layer (95 μm thick, 3.6 g / cm³) on both sides of the aluminum foil. 3 ), thus obtaining the positive pole.

[0191] (3) Preparation of non-aqueous electrolytes

[0192] LiPF6 and, as needed, 1,3-propenylsulfonyl lactone (PRES) were dissolved in a mixed solvent of EC, DMC, and MA (EC:DMC:MA = 20:60:20 (volume ratio)), and FEC was mixed in, thereby preparing a non-aqueous electrolyte. The concentration of LiPF6 in the non-aqueous electrolyte was set to 1.35 mol / L. The concentration of PRES in the non-aqueous electrolyte (the concentration at which the non-aqueous electrolyte was prepared) was set to the values ​​shown in Table 1 (mass %). The concentration of FEC in the non-aqueous electrolyte was set to 1 mass.

[0193] (4) Fabrication of non-aqueous electrolyte secondary batteries

[0194] An Al-made positive electrode lead is attached to the aforementioned positive electrode, and a Ni-made negative electrode lead is attached to the aforementioned negative electrode. In an inert gas atmosphere, the positive and negative electrodes are wound into a spiral shape with a polyethylene film (separator) in between, thus fabricating a wound electrode assembly. The electrode assembly is then housed in a bag-shaped outer casing formed from a laminated sheet having an Al layer. After injecting a predetermined amount of the aforementioned electrolyte, the outer casing is sealed to fabricate a non-aqueous electrolyte secondary battery. It should be noted that when the electrode assembly is housed in the outer casing, portions of the positive and negative electrode leads are exposed to the outside of the outer casing.

[0195] For the obtained non-aqueous electrolyte secondary battery, the negative electrode was removed using the method described above, and the porosity of the carbon composite particles (containing silicon material) was calculated. The results, along with the average pore size and specific surface area of ​​the carbon composite particles, are shown in Table 1. It should be noted that the average pore size and specific surface area were determined using a mercury porosimeter on the freshly prepared carbon composite particle powder.

[0196] "evaluate"

[0197] The obtained non-aqueous electrolyte secondary battery was evaluated as follows.

[0198] (1) Initial capacity

[0199] At 45°C, the battery was charged at a constant current of 0.5C (180mA) until the voltage of the non-aqueous electrolyte secondary battery reached 4.2V. Then, it was charged at a constant voltage of 4.2V until the current reached 0.05C (18mA). After a 10-minute rest period, it was discharged at a constant current of 0.7C (252mA) until the voltage of the non-aqueous electrolyte secondary battery reached 2.5V. The discharge capacity (Ci) at this point was calculated as the initial capacity.

[0200] (2) Cyclic characteristics

[0201] The cycle of charging, resting, and discharging at which the discharge capacity Ci is calculated is considered as one cycle. This cycle is repeated 100 times, and the discharge capacity (Cc) of the 100th cycle is calculated. The percentage (%) of the discharge capacity Cc when the initial discharge capacity Ci is set to 100% is calculated as the capacity retention rate X, which serves as an indicator of the cycle characteristics.

[0202] Capacity retention rate X (%) = (Cc / Ci) × 100

[0203] The results of the examples and comparative examples are shown in Table 1. In Table 1, A1 to A3 are Examples 1 to 3, and B1 to B6 are Comparative Examples 1 to 6. The capacity retention rate X is expressed as a relative value when the capacity retention rate X of Comparative Example 1 is set to 100.

[0204]

[0205] As shown in Table 1, high cycle retention rates can be obtained in batteries A1 to A3, which contain S-cyclic compound components in a non-aqueous electrolyte at a concentration range of 0.1% to 2% by mass and have a particle porosity of silicon-containing material of 6% to 20%.

[0206] Industrial availability

[0207] The non-aqueous electrolyte secondary battery disclosed herein is useful as a main power source for mobile communication devices, portable electronic devices, etc. However, these are merely illustrative examples, and the applications of non-aqueous electrolyte secondary batteries are not limited to these.

[0208] Preferred embodiments of the present invention have been described, but such disclosure is not intended to be limiting. Various modifications and alterations will be readily apparent to those skilled in the art upon reading the foregoing disclosure. Therefore, the scope of the appended claims should be interpreted as including all modifications and alterations without departing from the true spirit and scope of the invention.

[0209] Explanation of reference numerals in the attached figures

[0210] 1: Electrode assembly

[0211] 2: Positive lead

[0212] 3: Negative lead

[0213] 4: Battery casing

[0214] 5: Sealing board

[0215] 6: Negative extreme

[0216] 7: Padding

[0217] 8: Sealing plug

[0218] 30: Carbon composite particles

[0219] 301: Carbon phase

[0220] 302: Silicon phase

[0221] 303: Internal voids within particles

[0222] 33: Interparticle gaps

[0223] 34: External gap

Claims

1. A non-aqueous electrolyte secondary battery, comprising: a negative electrode containing a negative electrode compound, a separator, a positive electrode separated from the negative electrode by the separator, and a non-aqueous electrolyte. The negative electrode mixture contains negative electrode active substances. The negative electrode active material contains silicon. The internal porosity of the silicon-containing material particles is greater than 6% and less than 20%. The non-aqueous electrolyte contains a 5- or 6-membered cyclic compound component at a concentration of 0.1% to 2% by mass, wherein the 5- or 6-membered cyclic compound component contains sulfur as a constituent element of the ring.

2. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The silicon-containing material comprises carbon composite particles, wherein the carbon composite particles comprise a carbon phase and a silicon phase dispersed within the carbon phase.

3. The non-aqueous electrolyte secondary battery according to claim 2, wherein, The specific surface area of ​​the carbon composite particles is 5m². 2 / g or more and 20m 2 / g or less.

4. The non-aqueous electrolyte secondary battery according to claim 2, wherein, The average pore size of the carbon composite particles is greater than 1 nm and less than 45 nm.

5. The non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein, The cyclic compound composition comprises a cyclic compound containing sulfur as a constituent element of the ring and having carbon-carbon unsaturated bonds.

6. The non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein, The cyclic compound contains 1,3-propenylsulfonyl lactone.

7. The non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein, The silicon-containing material has a relative content of 0.5% to 20% by mass relative to the overall content of the negative electrode active material.

Citation Information

Patent Citations

  • Compound electrode material

    JP2014146519A

  • Game machine

    JP2024056205A

  • Anode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

    WO2010092815A1